2020
DOI: 10.1007/s10098-020-01942-8
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of an application possibility of geopolymer materials as thermal backfill for underground power cable system

Abstract: The circular economy is a closed cycle that allows one to reuse the industrial waste, as well as minimize the energy and resources losses during the production process. This paper presents an innovative idea of the application of a geopolymer cable backfill for underground power cable system installation. The closed cycle, in this case, is formulated as follows: the primary resource is the waste from the combustion of fossil fuels, i.e., fly ash that is utilized to form the geopolymer matrix. The geopolymer th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Thermal backfill materials have significantly higher thermal conductivity than the mother soil and can enhance the heat transfer from the buried power cables. In this case, the power cable temperature does not exceed a certain limit of the temperature [12,44,45]. In addition, an advantage of proper backfill material is the stability in time of its thermal conductivity [45].…”
Section: Soil Thermal Conductivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Thermal backfill materials have significantly higher thermal conductivity than the mother soil and can enhance the heat transfer from the buried power cables. In this case, the power cable temperature does not exceed a certain limit of the temperature [12,44,45]. In addition, an advantage of proper backfill material is the stability in time of its thermal conductivity [45].…”
Section: Soil Thermal Conductivitymentioning
confidence: 99%
“…Thermal assessment of an underground power cable is useful to obtain its ampacity, i.e., its current rating. This parameter represents the maximum electrical current flowing through an operated power cable conductor without exceeding the maximum limits of its operating temperature [12]. To calculate the power cable ampacity, it is necessary to evaluate some aspects that can affect the operational buried power cable characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Reference [10] calculated the conductor temperature for a typical water-cooled cable buried in a flat horizontal arrangement, and the simulation results showed that water-cooled pipes can effectively increase the ampacity. However, the thermal conductivity of water is not enough to meet the existing load demand, so existing studies have used different high-thermal-conductivity materials to reduce the thermal resistance of the external environment to improve the ampacity, and the improvement effect has been verified by experiments or finite element simulation [11][12][13][14][15][16][17][18][19]. In [20], an electromagnetic thermal coupling model of two parallel cables was established using the finite element method.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the temperature of the core conductor reduced from 64 ο C to 48 ο C, while the thermal conductivity of the surrounding back ll materials increased from 0.5 Wm − 1 K − 1 to 1.0 Wm − 1 K − 1 [12,13]. On the other hand, the improper dissipation of heat causes the migration of moisture from the vicinity of the power cable and thus, dry zone formation occurred due to loss of moisture causes thermal instability [15][16][17]. Therefore, the thermal back ll materials should have adequate thermal properties and favorable water retention capacity, which will facilitate the heat transfer easily from the heat source to the surrounding area with minimal moisture migration [18,19].…”
Section: Introductionmentioning
confidence: 99%